Chemically tunable photoresponse of ultrathin polypyrrole. Issue 23 (6th June 2017) - Wen, Peng; Tan, Changhui; Zhang, Junchang; Meng, Fanben; Jiang, Lin; Sun, Yinghui; Chen, Xiaodong
Abstract : A photoresponse of polypyrrole (PPy) based photodetector devices with ultrathin polymer layer can be chemically modulated by simply immersing the devices into an alkaline solution, and PPy belts with a width of 100 nm exhibit an ultra-high photosensitivites. Abstract : Building a complex structure system of conductive polymers without a complicated fabricating process is a long-awaited goal to improving the functional photoresponse properties of conductive polymers. In this study, we demonstrate that the photoresponse of polypyrrole (PPy)-based photodetector devices with an ultrathin polymer layer can be chemically modulated by simply immersing the devices into an alkaline solution. After alkaline treatment, the pyrrole unit transforms into a quinoid structure. Characteristics of current–voltage reveal an increased photosensitivity with several orders of magnitude when decreasing the applied bias voltage. Furthermore, ultrathin PPy belts with a width of 100 nm exhibit ultra-high photosensitivites of roughly 1000 (unit) and photoresponsivities of 54.3 A W −1 due to the high surface area ratio of the nanobelts.